Evaluating Patient Experiences and Perceptions in the Diagnosis and Management of Dentine Hypersensitivity: A Cross-Sectional Study: Patient Experiences in Dentine Hypersensitivity Management - Nayab, Tayyaba; Chaudhry, Ammara; Shaikh, Muhammad Saad; Ikram, Sana; Meraj, Nimra; Ijaz, Rabia (Pakistan Journal of Health Sciences, 2024)
Dentine Hypersensitivity (DH), or sensitive teeth, was a dental pain caused by exposure of dentinal tubules. Understanding patients’ experiences and perceptions was crucial for developing effective diagnostic and treatment plans. Objective: To investigate the patients’ experiences, perceptions, and diagnostic techniques for DH. The research also addresses the therapy approaches to limit dentine hypersensitivity for the better quality of life in patients. Methods: A non-probability convenience sampling technique was used to conduct the study for three months, from April 2024 to June 2024, in the University of Lahore’s dental hospital and private dental clinics in Lahore. A close-ended questionnaire consisting of 20 items was used for data collection. The relationship between DH, gender, and other variables was examined using a chi-square test; P-value < 0.05 was considered statistically significant. Results: The study with 1105 participants found a slightly higher representation of females (51%) than males (49%), with both genders reporting similar rates of tooth pain during food consumption. DH was most prevalent in the 41-60 age group (33.8%), with 74% experiencing pain with certain foods, 88% not receiving professional treatment, and 99% acknowledging DH’s significant impact on their quality of life. Conclusions: This study highlighted the significant prevalence of DH among adults, substantially impacting their quality of life. The findings emphasize the need for increased awareness, better diagnostic strategies, and patient-centred treatments to manage this condition effectively.